An analysis of the homicides in Hungary in the view of needs theories (Academic Journal of Internal Affairs, 2020)
Parallel investigations of needs theories and motivational theories - especially - as represented by Maslow’s hierarchy of needs on the one hand, and of the behaviour of criminals, more precisely, of the typical motivations and needs which drive the perpetrators of crimes to carry out a criminal act on the other hand- may yield interesting conclusions both from the perspective of criminal psychology and from the perspective of sociology. A comprehensive and thorough understanding of the characteristics of criminals and of the criminal acts they commit, as well as of the extent to which the needs of the perpetrators as individuals are being satisfied during the specific phase in their lives when the crime under scrutiny is being committed, considered together with the stress and frustration generated and with the need-driven patterns of behaviour and forms of conduct may lead to the elaboration of preventive strategies and predictive methods, as well as to the delivery of explanations which are capable of focusing on society while at the same time revealing individual preferences and specific factors underlying frustrations and involving potential solutions to these frustrations. After an overview of the scientific literature on motivational theory, my intention in this research is to align the above-mentioned categories of needs with the behavioural patterns of criminals identified during my research and with the data gathered regarding their social background; in the light of all these, an analysis will be made of the acts of murder and attempted murder which were committed in Hungary in the period between 2010 and 2014 and which were the subject of a definitive judgement. The question to which an answer is sought in this study is: whether it is justified to examine such criminal cases against the backdrop of the various needs theories, in particular that of Maslow’s hierarchy of needs, and whether a connection may be established between perpetrators’ motivations and the specific categories of needs as described in the theories. In the case of an affirmative answer to these questions, it will also be examined to what extent each of the needs appears to mpact on the behaviour of perpetrators.
Keywords: need-category; Maslow; need-satisfaction; criminal psychology